Alienating: how the portrayal of Muslim women in US media affects Muslim women’s social identities - Issaka, Barikisu (Kansas State University, 2021)
Among the portrayals of the minorities in general and Muslims, men and women, in particular in the U.S., Muslim women have been noted to be the most misrepresented and negatively framed. Although previous studies have highlighted the effects of media framing on minorites including their identities, little research exists which analyzes how Muslim women are portrayed in US women from the women’s perspectives and how these portraysls affect the women’s social identities. Accordingly, this phenomenological research sought to fill the gap in the literature through an examination of how Muslim women are portrayed in US media and the impact of such portrayals of their social identities. This study employed a qualititve approach through in-depth semi structured interviews and framing theory and social identities theory as the theoretical frameworks. The study found that the negative framing and misrepresentations of Muslim women in the mainstream media are widespread and cut across themes such as victims of oppression, lack of agency, and underrepresentation. From the women’s perspective, these do not reflect their realities. Yet, such negative portrayals have adverse consequences on the women’s social identities such that they lead to identity threats. These identity threats compel the women to compare themselves to other majority/minority groups such as Christians and Jews. To cope with such identity threats, some of the women dissociate from their Muslim ingroup and its identity markers such as the wearing of the hijab; others associate with the ingroup and its identity markers; and almost all of them avoid mainstream media. The theoretical and practical implications of this phenomenon are highlighted.
Keywords: US media; Muslim women; Social identities; FramingMedia portrayals